[ Arts] tigma: Curating a public platform for arts production and exhibition in Troyeville - Mthimkhulu, Boitumelo Nicol (My University, 2013)
The premise of this essay is to oppose the local notion of the arts as exclusive, while exploring the potential integration of the arts to impact the architectural production of public space, both in the physical and psyche…. The focus of this essay is on the exploration of the impact of art in the architectural design of public space. I intend to explore the presence, impact and use of art and culture in the context of Johannesburg and its surrounding suburbs. The intention is to use this essay as an initiating literature review with the objective to discuss and compare different arguments pertaining to the subject of art and architecture and their literal and imagined attitudes towards public space. I will specifically make reference to the existing theories of art and architecture through the years. With the aims of the outcomes being one that defines a new public space language appropriate to current cultural practice, the availability of resources and the position of the local Johannneburg art scene. I will question whether public space should be created for the users of the city or if the people should have the power to determine the functions of their public space.